Hadith Muhammad's legacy in the medieval and modern world - Brown, Jonathan A.C. (London, England Oneworld Publications, 2018)
'It is impossible to understand the Islamic tradition without getting some knowledge of the sciences of hadith. In this fascinating introduction, Jonathan A. C. Brown provides the reader with the necessary means to navigate between the traditional framework and contemporary issues. A brilliant essay was written by a widely-acknowledged scholar in the field.' -- Tariq Ramadan, Professor of Contemporary Islamic Studies, University of Oxford 'Far surpasses all previous introductory surveys. It is especially distinguished by its attention to hadith scholarship throughout the Middle Ages, not just the age of the great collectors.' -- Christopher Melchert, Professor of Arabic and Islamic Studies, University of Oxford 'A must read and a great read. The combination of impeccable, critical scholarship with a storyteller's style has produced an introductory volume that is both substantive and remarkably engaging.' -- John L. Esposito, Founding Director of the Center for Muslim-Christian Understanding at Georgetown University 'A comprehensive study of the scholarship throughout Islamic history dealing with the traditions of the Prophet. A combination of critical analysis and informed understanding that presents a significant new perspective on a much-debated subject.' -- John O. Voll, Professor Emeritus of Islamic History, Georgetown University 'This work is, in my opinion, without parallel in the English language. Stunning in its scope, it enables one to grasp a highly complex subject in well-written and clear prose. The knowledge of Islam is of utmost importance today, and this book bridges a yawning gap in our access to that knowledge in English. It's essential reading for any serious student of Islam limited by language.' -- Hamza Yusuf Hanson, president, and co-founder, Zaytuna College
Keywords: Hadith -- History; Islamic law -- History